1991
DOI: 10.1007/bf00315211
|View full text |Cite
|
Sign up to set email alerts
|

Chronopharmacokinetics of doxorubicin in patients with breast cancer

Abstract: The chronopharmacokinetics of doxorubicin (DOX) has been studied in 18 patients suffering from breast cancer. They received combined chemotherapy including DOX (50 mg/m2 as an iv bolus), given at two different times (09.00 h or 21.00 h). The two randomized courses of the protocol were given to each patient at a four week interval. The total body clearance (CL) of DOX was significantly decreased when the drug was administered at 21.00 h, resulting in a longer elimination half-life and an increase in AUC. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Circadian timing significantly influences the plasma and/or urinary pharmacokinetics of intravenously administered 5-fluorouracil, methotrexate, doxorubicin, epirubicin, and cisplatin in cancer patients (125)(126)(127)(128)(129)(130). This is also the case for orally administered busulfan, 6-mercaptopurine, and tegafur/uracil (120,(131)(132)(133)(134).…”
Section: Spontaneous or Imposed Circadian Control Of Anticancer Drug mentioning
confidence: 92%
“…Circadian timing significantly influences the plasma and/or urinary pharmacokinetics of intravenously administered 5-fluorouracil, methotrexate, doxorubicin, epirubicin, and cisplatin in cancer patients (125)(126)(127)(128)(129)(130). This is also the case for orally administered busulfan, 6-mercaptopurine, and tegafur/uracil (120,(131)(132)(133)(134).…”
Section: Spontaneous or Imposed Circadian Control Of Anticancer Drug mentioning
confidence: 92%
“…A circadian phase dependency has also been reported for the pharmacokinetics of other protease inhibitors, as well as other widely used drugs (e.g. digoxin, doxorubicin, gentamicin, nifedipine) [6–10].…”
Section: Introductionmentioning
confidence: 99%
“…2). In addition, many researchers suggested that the pharmacokinetics of anti-cancer drugs, doxorubicin and tamoxifen, exhibit circadian variations [35,36]. In this study, sensitivity to doxorubicin and tamoxifen also increased upon co-treatment of KS15 ( Fig.…”
Section: Discussionmentioning
confidence: 78%